A Statistical analysis on the case of rejection of sanitary gray Unplasticized Polyvinyl Chloride (UPVC) Pipes of Century Pipes Corp. - Abanto, Ray Anthony A.; Moral, Ernie II.; Santos, Rowell Angelo (Diliman, Quezon City College of Engineering, 2002)
Statistical methods are used in a wide variety of occupations and help people identify, study and solve many complex problems. In the business and economic world, these methods enable decision makers and managers to make informed and better decisions about uncertain situations. Statistical data analysis simplifies the interpretation of a certain phenomenon with high degree of reliability. Hence, statistical data analysis is important in the area of decision making process because it facilitates managers and decision makers to make educated decisions in the business world. Most machine-intensive manufacturing company are prone to high rates of rejects during their manufacturing cycle, regardless of how well designed or carefully maintained, due to inevitable errors inherent during their production processes. Century Pipes Corporation is one such company whose line of business is manufacturing uPVC pipes. This experimental study examines the present production and quality system being employed by the company with the objectives of determining which factors contribute to high percentage of rejects during their production of uPVC pipes. A high rate of rejection occurs during their extrusion process mainly because of the complexity of the machine, in terms of process parameters being maintained. During this stage of the production, several failure modes (i.e. ovality, cracks, waviness, color, blisters, and non-uniform thickness) occur which serves as basis for rejection. It was determined that non-uniform thickness, particularly the outer diameter within the pipes contributes the highest variability during the said process. Statistical procedures were applied in gathering data for further analysis. Based on theories of statistical data analysis, this paper tests an experimental design to determine if the controllable parameters : screw temperature, feeder line speed, and motor line speed of the extrusion process exhibit significant effects on the outer diameter of the pipe (response variable), the high contributor of rejects. The power of the test was conducted in order to see how reliable the experiment will be. The data was tested if it was randomly and normally distributed. This is in congruence with the requirements of the performance of an analysis of variance. The tests yielded a positive response. Thus, analysis of variance, a significance test, was performed to validate which main factors or factor interactions significantly affect the response variable. Results indicated that interaction between the screw temperature and motor line speed as well as the interaction between feeder line speed and motor line speed has a significant effect on the outer diameter yields. Through a Residual Analysis, the research group was able to determine the best contamination of each of the factor's settings that yielded the least variability from the tolerance limit for the pipe's outside diameter. The result yielded a low variability if the level for the temperature was high and low for the feeder line speed and motor line speed. The company can lessen their rates of rejection, in terms of the outside diameter of the pipe, and hence, improve their level of productivity by exploiting such setting combination. It is therefore recommended that company deal into this result by controlling its factors and setting it to the levels stated above. Reiterating, the setting employs the combination of a high temperature (190 degree celcius), low feeder line speed (8 x 100 rpm) and low motor line speed (11 x 100 rpm).
Feasibility study.
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics